2021
DOI: 10.1101/2021.06.10.447863
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Consciousness Theories Studies (ConTraSt) database: analyzing and comparing empirical studies of consciousness theories

Abstract: Understanding how consciousness arises from neural activity remains one of the biggest challenges for neuroscience. Numerous theories have been proposed in recent years, each gaining independent empirical support. Currently, there is no comprehensive, quantitative and theory-neutral overview of the field that enables an evaluation of how theoretical frameworks interact with empirical research. We provide a bird's eye view on studies that interpreted their findings in light of at least one of four leading neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Further relevant epistemological and methodological challenges implicated in consciousness research need to be carefully addressed, with the importance for experiments to question given theories, rather than merely attempting to support them. In this respect, Yaron et al (2021) have considered a large set of studies that interpreted their findings with reference to as least one of four leading neuroscientific theories of consciousness. They found that supporting a specific theory can be predicted solely from methodological choices, irrespective of findings, and that, furthermore, most studies interpreted their findings post-hoc, rather than a-priori testing critical predictions of the theories.…”
Section: Discussionmentioning
confidence: 99%
“…Further relevant epistemological and methodological challenges implicated in consciousness research need to be carefully addressed, with the importance for experiments to question given theories, rather than merely attempting to support them. In this respect, Yaron et al (2021) have considered a large set of studies that interpreted their findings with reference to as least one of four leading neuroscientific theories of consciousness. They found that supporting a specific theory can be predicted solely from methodological choices, irrespective of findings, and that, furthermore, most studies interpreted their findings post-hoc, rather than a-priori testing critical predictions of the theories.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, in addition to controlling for as many confounding factors as possible within a single study, it will be necessary to perform multiple studies to cross-validate the results: a research program that will take years and significant collective effort to complete. This problem has been noted and acknowledged by the scientific community, and its impact on the theories is just now starting to be grasped (Yaron et al, 2021). For instance, there is growing empirical evidence that the P3b, a marker once thought to reflect the broadcasting of information into the global workspace (Sergent et al, 2005), might instead reflect post-perceptual processes (Forster et al, 2020).…”
Section: Methodological Challenge: More Than One Nccmentioning
confidence: 99%
“…An initial step towards this goal will simply be to aggregate the preexisting data reported in the literature into common databases, gathering data across different studies, including all research modalities, in order to create an interactive, communityaugmented meta-analysis tool for the science of consciousness (for similar efforts in other communities, see http://metalab.stanford.edu). This effort will enable a completely new cartography of the field as well as a theoretically neutral perspective allowing us to identify tendencies, such as whether theories rely on all experimental paradigms or only a handful of them, etc (Yaron et al, 2021). The ultimate goal, however, is much more ambitious: the capacity to share raw and/or unthresholded data across investigators (including metadata).…”
Section: The Need For Big Datamentioning
confidence: 99%
“…However, the existence of common goals does not prevent researchers from following new leads, as in standard scientific practice. Instead, they can help break tendencies to seek only confirmatory evidence for one’s favorite theories (Yaron et al, 2021) and enable adversarial collaborations in which researchers from different camps work together to resolve their differences (Melloni et al, 2021).…”
Section: Potential Drawbacks Of Common Goal Settingmentioning
confidence: 99%